Unity in Variety--The Pan-Genome of the Chlamydiae - Astrid Collingro; Patrick Tischler; Thomas Weinmaier; Thomas Penz; Eva Heinz; R C Brunham; Timothy D. Read; Patrik M. Bavoil; Konrad Sachse; S. Kahane; Maureen G. Friedman; Thomas Rattei; et al. (2011)
Chlamydiae are evolutionarily well-separated bacteria that live exclusively within eukaryotic host cells. They include important human pathogens such as Chlamydia trachomatis as well as symbionts of protozoa. As these bacteria are experimentally challenging and genetically intractable, our knowledge about them is still limited. In this study, we obtained the genome sequences of Simkania negevensis Z, Waddlia chondrophila 2032/99, and Parachlamydia acanthamoebae UV-7. This enabled us to perform the first comprehensive comparative and phylogenomic analysis of representative members of four major families of the Chlamydiae, including the Chlamydiaceae. We identified a surprisingly large core gene set present in all genomes and a high number of diverse accessory genes in those Chlamydiae that do not primarily infect humans or animals, including a chemosensory system in P. acanthamoebae and a type IV secretion system. In S. negevensis, the type IV secretion system is encoded on a large conjugative plasmid (pSn, 132 kb). Phylogenetic analyses suggested that a plasmid similar to the S. negevensis plasmid was originally acquired by the last common ancestor of all four families and that it was subsequently reduced, integrated into the chromosome, or lost during diversification, ultimately giving rise to the extant virulence-associated plasmid of pathogenic chlamydiae. Other virulence factors, including a type III secretion system, are conserved among the Chlamydiae to variable degrees and together with differences in the composition of the cell wall reflect adaptation to different host cells including convergent evolution among the four chlamydial families. Phylogenomic analysis focusing on chlamydial proteins with homology to plant proteins provided evidence for the acquisition of 53 chlamydial genes by a plant progenitor, lending further support for the hypothesis of an early interaction between a chlamydial ancestor and the primary photosynthetic eukaryote.